PEMBANGUNAN PERTANIAN: SEBUAH KAJIAN PUSTAKA TERSTUKTUR - Wijaya, Wahyu Rizal; Salahudin, Salahudin (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
This study aims to examine more deeply about agricultural development. This study uses the systematic literature review method, articles taken from the publications of various publishers using the SCOPUS database and given restrictions on the year of publication only for the last two years or the same as from 2019 to 2021. From the results of this search resulted in 233 views of relevant articles. With this research topic, this figure is obtained from the number of files (.ris) that are exported to Mendeley software. This study explains that agricultural development is currently an integral part of the general public. In agricultural development, it is not only a process or activity of agricultural production but also something that can produce social changes from the scope of values, norms, behavior, institutions, social and so on in order to achieve better economic growth and improve the welfare of farmers and society to become more and more. The limitations of this study are examples of articles presented that differ from the existing conditions in each country so that there is a need for a critical understanding of the government system in the examples of articles that are used as references besides that there needs to be special considerations in determining equations and new findings from articles that are used as reference material to develop the main idea in accordance with the selected topic and title so that the next research needs to understand the main points of the topics that are in accordance with the title and focus on research by adjusting to new things that are to be sought and can be adjusted to the title that is raised.